Language as Social Identity: A Study of Linguistic Landscape in Meulaboh, West Aceh - Istika Suri; Frans Asisi Datang (Faculty of Social Science, Universitas Negeri Malang, 2024)
The language used in public spaces is closely related to the social identity of the community. This study examines the linguistic landscape of Meulaboh City by analyzing public signs and their connection to the local community’s identity. The method used is a descriptive qualitative approach, with data consisting of 121 photos collected from several streets in Meulaboh, West Aceh Regency, including government buildings, schools, billboards, and other notable features. The findings reveal three types of signage: monolingual, bilingual, and multilingual, with a dominance of Indonesian-English usage. These findings demonstrate that language in public spaces serves not only as a tool for communication but also reflects the local community’s social and cultural identity. English is more commonly used in business contexts, while Indonesian dominates formal domains such as government offices and schools. Regional identity is not strongly reflected in the linguistic landscape of West Aceh, except in traditional eateries and coffee shops that still use the Acehnese language.